The Socialization Headmaster To Learning Covid-19 At Madrasah Darussalam Foundation Gunung Tua - Muhammad Fuad Zaini, Indah Melia Putri Siregar (Journal of Education and Teaching Learning, 2021)
The impact that occurs on learning in every school is greatly affected by the Covid-19 pandemic. This study reveals how the learning situation during the pandemic at the Madrasah Darussalam Foundation, Gunung Tua Paluta. In this study, the method used is a qualitative research method with this method intended to find more factual data in the field for further analysis. As for the results of the study, the difficulties of teachers in conducting online learning in madrasas, difficulties in understanding by students, especially arithmetic subjects. student achievement and grades tend to experience a continuous and overall decline. online learning hurts the entire academic community in madrasa